Causal contributors to tissue stiffness and clinical relevance in urology - Laura Martinez-Vidal (Nature Portfolio, 2021)
In this Review, Laura Martinez-Vidal et al. summarize current knowledge of factors affecting extracellular matrix (ECM) remodeling in the context of pathological mechanical changes to tissue properties. They focus on the importance of research on tissue stiffness to the development of diagnostic tools and therapies to treat urological disease.